Teigne Tondante and Mahon brothers: Two laymen "physicians" of Hôpital Saint-Louis, Paris - Amiya Kumar Mukhopadhyay (Wolters Kluwer Medknow Publications, 2018)
In the early and mid-nineteenth century Europe, ringworm of the scalp was a vexing problem. It affected children in such numbers that the famous Hôpital Saint-Louis of Paris had a separate Tinea School. Before advent of radiation method of epilation, painful method of peeling was the mainstay of management. A family bearing title Mahon with no conventional medical training and qualification developed a secret method of epilation which was far superior to the existing method of treatment. Two brothers of this family, whose identity is obscure in the history of dermatology, were given the charge of treatment of such cases in various hospitals of France. Though they were not physician per se, their observations surprise us even today. Mahon the junior wrote a book on ringworm which is the first ever monograph on the subject. They also described favus of the nail and named ringworm of the scalp.